Australian screen studies: pedagogical uses of Australian content in tertiary education. Issue 1 (2nd January 2018) - Ryan, Mark David
ABSTRACT: Australian screen studies courses, including 'Australian Cinema', 'Australian National Cinema', 'Australian Film', and 'Australian Film and Television', among others, have long been offered in the creative arts, education, humanities and social sciences in Australian higher education. At the core of these courses' curricula is viewing and studying movies, documentaries, and television programmes. However, despite recent research into broad curriculum models, there has been limited scholarly examination of pedagogical practices regarding the use of Australian screen content for teaching and learning purposes in these courses. The research investigates three key issues: how coordinators source and deliver Australian content for screening programmes; the views of the coordinators in relation to the relevance of an institutional film canon for pedagogy; and the coordinators' perspectives on the importance of Australian screen history and the role it plays in pedagogy and curricula. The findings are drawn from 10 semi-structured interviews with the principal coordinators of undergraduate Australian screen courses at a range of universities across those states and territories that did offer undergraduate Australian screen courses.